Development of functional health nanodrinks based on milk whey - Павлюк, Раиса Юрьевна; Погарская, Виктория Вадимовна; Абрамова, Татьяна Сергеевна; Берестовая, Аделина Анатольевна; Лосева, Светлана Михайловна (Eastern-European Journal of Enterprise Technologies, 2014)
The aim of scientific work is the development of the recipe, experimental objectivation of technological regimes, process flowsheet and technology of new drinks based on whey with the use of fine-dispersed frozen additives containing pumpkin, sea buckthorn, bananas in the nanostructured puree form, and also phytoextracts based on natural spices; studying the content of biologically active substances in the new drinks in comparison with analogues; studying quality of the drinks during the storage; development of regulatory documentation; approbation of the new drinks in industrial environment. Technology and technological process regimes of new types of milk-herbal drinks based on whey are developed and scientifically explained. The new drinks differ from the traditional ones by the addition of frozen fine-dispersed fruit and vegetable additives into the boiling sugar syrup. Simultaneously defrostation and thermal processing of fruit and vegetable raw materials occur which guarantee the fullest preservation of biologically active and aromatic substances, conservation of natural flavor. It is found that the drinks have stable homogeneous consistency which does not separate due to the fact that the introduction of additives from pumpkin, buckthorn and bananas have the properties of structurants and thickeners. The results were confirmed by IR spectroscopic analysis, which demonstrated that new lactic herbal drinks are 2 times longer stored and the content of BAS such as ascorbic acid, phenol compounds, tannins, pectin, essential amino acids, etc. Exceed the known analogues and possess potential immunomodulatory properties. Thus, they can be referred to as health products recommended for healthy diet. On the basis of the results was made possible development of the Scientific Research Project on nanostructured frozen puree. New types of drinks were degustated and approbated in industrial environment of Kharkov (Ukraine): Ltd "Bogodukhov milk factory" Ltd SUIS "Polyus Ltd".